‘That’s why an artwork should have a national character’: The Incasso Banks of Gratama and Dinger (Bulletin KNOB, 2023)
Between 1929 and 1938 the Gratama and Dinger architectural practice produced a great many branch offices for the Incasso Bank. Jan Gratama (1877-1947) was responsible for their design. Internationally, the year 1929 was of enormous economic and political importance. The stock market crash in New York, ushered in by Black Thursday on 24 October, caused share prices worldwide to plummet. The immediate consequence was the Great Depression of the 1930s. Banks failed, debts piled up and many Dutch households ran into financial difficulties. This volatile climate was an ideal political breeding ground for splinter parties opposed to parliamentary democracy. One of those parties was the Nationaal-Socialistische Beweging (National Socialist Movement, NSB), which attracted a lot of adherents in the 1930s. This article discusses Gratama’s designs for the Incasso Bank and their position within his body of work against the backdrop of the political developments of the 1930s.Although it is tempting to see Gratama’s application of classicism as a consequence of his political ideas, such a connection cannot be established with certainty. Many passages in his writings on traditional and modern architecture suggest an association with national socialism. But as far as is known, Gratama never explicitly linked his building style to his political convictions, apart from expressions like ‘national character’ and ‘tradition’. Moreover, as a political movement Dutch national socialism itself had expressed no preference for a particular architectural style.It is more likely that the Incasso Bank’s commercial need to project reliability and a trusted identity in economically uncertain times happened to coincide with Gratama’s retreat into an historicizing architectural style that he evidently viewed as an appropriate response to the economic and political events of the 1930s. The steady stream of commissions from the Incasso Bank meant that he was able to apply that style in practice and to continue to develop it. As such, his buildings for the Incasso Bank are above all the expression of his architectural development in the 1930s, a development made possible almost entirely by his commissions for the Incasso Bank.